Clinical and Histopathological Criteria in Libyan Children with Adrenocortical Tumors - Omalmir Fathalla; Millad Ghawil; Ahmed Eshagroni; Nadia Alghazir; Ibtisam Hadeed; Amani Farhat; Amani Masoud (AlQalam Journal of Medical and Applied Sciences, 2025)
Adrenocortical tumors (ACTs) are rare in children, and the extent to which histopathological features can predict clinical behavior remains uncertain. This study aimed to investigate the relationship between histopathological features, surgical approach, tumor size, and outcome by reviewing medical records from 2008 to 2024 of patients treated at Tripoli University Hospital. About 10 ACTs were treated at our institution. We identified them from a database that included demographic and clinical characteristics. The histological features were documented in their medical files. Ten patients were treated for ACTs with a mean age of 2 years (range from 12 months - 17 years). 4 (40%) of them were diagnosed with adrenocortical carcinoma, and 6 patients (60%) were diagnosed with adrenocortical adenoma. In addition, 80% of tumors were on the right side, and 7 patients (70%) survived without evidence of disease, and 3 patients (30%) died. There is an association between histopathological classification, tumor size, and outcome for pediatric ACTs. Pediatric ACTs’ histopathological findings, early complete surgical resection is optimal for a good outcome. Genetic evaluation is recommended in patients with ACTs.